Selective etching of epitaxial MnAs films on GaAs(001): Influence of structure and strain - Mohanty, J; Takagaki, Y; Hesjedal, T; Daweritz, L; Ploog, K (2005)
Strain in epitaxial MnAs thin films on GaAs(001) substrates plays an important role in the coupled magnetostructural phase transition. As a result of strain, the phase transition from the ferromagnetic α phase to the paramagnetic Β phase proceeds over a wide temperature range and the coexisting phases form a periodic stripe array. Employing suitable wet chemical etchants, the two MnAs phases can be etched selectively. Perpendicular to the α-Β -stripe structure, the built-up strain relaxes in the course of the etching process by the formation of cracks. The combination of both strain relaxation mechanisms allows for the defined patterning of two-dimensional arrays of nanomagnets. Through micromagnetic investigations, it is possible to identify the location of α - and Β-MnAs which helps to clarify two major aspects of the etching process. First, it is possible to determine the etch rates of α - and Β-MnAs and follow the complex interplay of strain and phase composition during the etching process. Second, as strain reflects itself in a shifted phase-transition temperature, temperature-dependent micromagnetic studies allow to determine the strain environment of the cracks. © 2005 American Institute of Physics.